Performance of Channel Estimation in MIMO-OFDM Systems - Subuh Pramono; Eddy Triyono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
This paper presented the performance of faded channel estimation method on orthogonal frequency division multiplexing-multiple input multiple outputs (OFDM-MIMO) i.e. least squares (LS) and minimum mean squared error (MMSE). Channel impuls response (CIR) was  required to overcome the intersymbol interference (ISI). Channel impuls response information was obtained from channel estimation processing. Iterance simulation used monte-carlo technique to determine the performance of bit error rate (BER) and mean squared error (MSE). Simulation results show that the mean squared error performance on MIMO system was better than the SISO system. On MMSE channel estimation, the MIMO 2Tx-2Rx system provided ± 2 dB improvement that compared to SISO system at value of MSE 10-2.Furthermore,MIMO 3Tx-2Rx produce improvement about 1.5 dB, MIMO 4Tx-2Rx improve about 3.5 dB at BER 10-4,respectively.The MIMO 2Tx-2Rx system, MMSE channel estimation produced better performance ± 1 dB than LS channel estimation with sufficient SNR value for MSE 10-2 .Pilot arrangement, the simulation results show that the block type-pilot arrangement produced better performance than the comb type-pilot arrangement at fast fading channel. Block type-pilot arrangement system produced better ± 10 dB than the comb type-pilot arrangement with MMSE method at value of BER 2 10-2.